2021
DOI: 10.1093/scan/nsab005
|View full text |Cite
|
Sign up to set email alerts
|

Reported maternal childhood maltreatment experiences, amygdala activation and functional connectivity to infant cry

Abstract: Maternal childhood maltreatment experiences (CMEs) may influence responses to infants and affect child outcomes. We examined associations between CME and mothers’ neural responses and functional connectivity to infant distress. We hypothesized that mothers with greater CME would exhibit higher amygdala reactivity and amygdala–supplementary motor area (SMA) functional connectivity to own infant’s cries. Postpartum mothers (N = 57) assessed for CME completed an functional magnetic resonance imaging task with cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…This area has drawn attentions because of a series of clinical deficits caused by its resection or damage, including abnormal motor integration, recognition of movement and thinking, memory storage, language production, conflict resolution, intention of action (Bozkurt et al, 2016; Coull, Vidal, Nazarian, & Macar, 2004; Kennerley, Sakai, & Rushworth, 2004; Mayka, Corcos, Leurgans, & Vaillancourt, 2006). The SMA also presented emotion and memory-related neural activity changes in people with a history of childhood trauma (Elton, Smitherman, Young, & Kilts, 2015; Lim et al, 2015; Ma et al, 2021; Olsavsky, Stoddard, Erhart, Tribble, & Kim, 2021). The left parahippocampal gyrus revealed GMV reductions solely in the adult sample in our results.…”
Section: Discussionmentioning
confidence: 99%
“…This area has drawn attentions because of a series of clinical deficits caused by its resection or damage, including abnormal motor integration, recognition of movement and thinking, memory storage, language production, conflict resolution, intention of action (Bozkurt et al, 2016; Coull, Vidal, Nazarian, & Macar, 2004; Kennerley, Sakai, & Rushworth, 2004; Mayka, Corcos, Leurgans, & Vaillancourt, 2006). The SMA also presented emotion and memory-related neural activity changes in people with a history of childhood trauma (Elton, Smitherman, Young, & Kilts, 2015; Lim et al, 2015; Ma et al, 2021; Olsavsky, Stoddard, Erhart, Tribble, & Kim, 2021). The left parahippocampal gyrus revealed GMV reductions solely in the adult sample in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Across continents and cultures, the SMA was highlighted in response to own vs. other baby-cry for infant-oriented preparation for movement and vocalization (Bornstein et al, 2017) and also demonstrated to be important for child-oriented empathy in a parent decision-making fMRI task (Ho et al, 2014). Finally, SMA connectivity to amygdala was reported to be heightened during maternal responses to infant distress according to maternal childhood maltreatment and decreased maternal intrusive behaviors, suggesting the potential for transgenerational adaptations to early life adversity that could include brain responses and infant-oriented behaviors to increase maternal sensitivity (Olsavsky et al, 2021). Perhaps plasticity in the SMA could be a future target for interventions to address maternal health from early childhood maltreatment to OUD such as transcranial magnetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…use of incorrect stimuli). An overlapping sample of fMRI data from the current study has been included in prior publications 30 , 69 , 81 , 82 , however, the current research question has not been examined.…”
Section: Methodsmentioning
confidence: 99%